The Botanic Gardens, Port of Spain, Trinidad - (:unkn) unknown (My University, 2010)
The postcard shows a pathway among the varieties of trees in the Botanical Gardens in Trinidad.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Palms--Trinidad and Tobago; Plants--Trinidad and Tobago